Analysis of Factors Influencing Intention to Purchase “Portable Fire Extinguisher” for Residential House in DKI Jakarta - Oktovani, Theresia; Arief Bowo Prayoga Kasmo (Dinasti Publisher, 2023)
This study aims to analyze the factors that influence the intention to buy Fire Extinguisher products for residential homes in DKI Jakarta area. These factors include Awareness, Knowledge, and Perceived Price as independent variables. Attitude as an intervening variable, and Purchase Intention as the dependent variable. The population of this study is households living in DKI Jakarta, with a total sample of 150 people who will be taken through a questionnaire instrument. The data analysis method uses Structural Equation Model–Partial Least Square (SEM-PLS) which will be processed using Smart-PLS software. The results of the study show that there is a positive and significant influence between the independent variables namely Awareness, Knowledge, and Perceived Price on the dependent variable Purchase Intention. Attitude as an intervening variable can mediate the independent variables on the dependent variable.